MUBEM & SAC: STEM Based Science and Nature Camp - Hasan Zuhtu Okulu; Ayse Oguz-Unver; Sertac Arabacioglu (Journal of Education in Science, Environment and Health)
The idea behind the MUBEM & SAC: STEM based science and nature camp was a transformation of scientific knowledge into artifacts using the engineering design process and scientific inquiry. The goals of the camp were developing an integrative science perspective in accordance with the nature of STEM education, supporting career choices of participants for STEM fields, experiencing outdoor learning environments and researches with real scientists, internalizing engineering design process by creating artifacts, and comprehending interaction with nature and science. The participants were sixth and seventh grades gifted students (Male: 14 and Female: 15). STEM attitude scale, researcher notes, artifact, camp, and activity evaluation forms were used as data collection tools. The several disciplines such as astronomy, archeology, music, and mathematics involved the camp. The participants found the opportunity to use telescopes, experience an extensive archaeological excavation, observe the near-nano size object with electron microscopes, construct a bridge like an engineer, and design artifacts like rockets and holograms during the camp. According to results, the science and nature camp supported participants’ STEM attitudes and participants' views on the science and nature camp were positive. In addition, participants' artifacts were also qualified as STEM artifacts.